GATA3 regulates FLG and FLG2 expression in human primary keratinocytes - Jana Zeitvogel (Nature Portfolio, 2017)
Abstract GATA3 is a transcription factor with an important role in atopic diseases because of its role in the differentiation of Th2 lymphocytes. Moreover, GATA3 is expressed in keratinocytes and has a role in keratinocyte differentiation and the establishment of the epidermal barrier. In this study, we investigated the role of GATA3 in keratinocytes in the context of epidermal barrier integrity under inflammatory skin conditions. When analysing skin samples from atopic dermatitis and psoriasis patients or healthy controls, we detected decreased expression of GATA3 in the stratum spinosum and stratum granulosum of atopic dermatitis and psoriasis patients when compared to healthy controls. Our cell cultures experiments revealed that a downregulation in GATA3 by shRNA leads to a significant reduction of filaggrin mRNA under atopic dermatitis-like conditions in keratinocytes. Overexpression of GATA3 in keratinocytes reversed this effect and significantly upregulated filaggrin and, furthermore, filaggrin-2 mRNA expression. Our results demonstrate that GATA3 is involved in the regulation of filaggrin and filaggrin-2 expression during inflammatory conditions in the skin. Thus, GATA3 may be of special importance for the establishment and maintenance of an intact epidermal barrier, especially in atopic dermatitis.